Rancang Bangun Sistem Kendali Rumah Jarak Jauh Menggunakan Telepon Selular Android - ., Sultan Fiqri (Jurnal Teknik Elektro Universitas Tanjungpura, 2014)
Abstract– One reason for the emergence of the remote control system is the need of the people would be the appropriate technology that can make the job easier and can also reduce the risk of theft and robbery. In this thesis designed an electronic technology that can control home electronic devices remotely as much  6 points using Relay and monitor the condition of open and close of the door as much 6 point using switches and to monitor existance of the intruder side of the building sector in the home by using PIR sensor as much 1 point. This system is divided into two parts, namely software and hardware. The software is an embedded application on an Android phone that is functionalized for home control device by long distance. While the hardware is enabled to process orders and execute orders, the hardware is installed in the home that want to be controlled. From the test results, the remote control system obtained an average response time of 3 seconds to be able to control electronics device and when the sensor is active it takes an average of 4 seconds to be able to watch the response in android application. From the results of experiments conducted remote home control system using android mobile phone that is designed to work well with a fast response time and can help to show the condition of the house and save the data in the phone database, so the data will not be lost when the application is closed.   Keywords– Android, Remote Control, Relay, Switch, PIR Sensor.